Invasive plant and honeybee alter native plant-pollinator network structure in dry forest - RODRIGO F. R. CARMO; CÁSSIO H. CARVALHO; REGINALDO A.F. GUSMÃO; LUCAS F.C.S. ALENCAR; JEFERSON VIZENTIN-BUGONI; GABRIEL X. BOLDORINI; GABRIELA A. GALVÃO; JOYCE C.B. BRITO; THIAGO GONÇALVES-SOUZA (Anais da Academia Brasileira de Ciências)
Abstract Invasive species pose a critical threat to ecosystems, with far-reaching consequences. Invasive plants can directly interact with native pollinators, while wind-pollinated grasses indirectly alter plant-pollinator networks by reshaping the composition of plant and animal communities, diminishing ecosystem functioning. Here, we investigated the effect of invasive grass on pollinator richness, native plant visits, and the structure of plant-pollinator networks. Additionally, we explored the influence of non-native honeybees on these same variables in the Caatinga. Invasive grass negatively affected native pollinators and reduced visitation to native plants. The dominance of invasive grass leads to an increased niche overlap among native pollinators. Surprisingly, this did not affect the number of visits by non-native honeybees. However, the increased honeybee visitation negatively impacted native pollinator richness, causing a 60% decline. Our results underscore the compounded negative effects of invasive grass and non-native honeybees on native plant-pollinator dynamics. Invasive grasses indirectly decrease pollinator visits by altering plant communities. Meanwhile, honeybees, unaffected by invasive grass, decrease native pollinator species’ richness and visitation rates. These findings emphasize the significant impact of biological invasions on ecosystem health, shedding light on the complex interplay between invasive species and plant-pollinator interactions in arid, abandoned landscapes.